2020
DOI: 10.1016/j.ajic.2019.06.017
|View full text |Cite
|
Sign up to set email alerts
|

Assessing sustainability of hand hygiene adherence 5 years after a contest-based intervention in 3 Japanese hospitals

Abstract: Background: Our goal was to evaluate the 5-year sustainability of a multimodal intervention that included a prize to the hospital with the highest overall hand hygiene adherence rates among health care workers. Methods: We conducted an observational study in 3 Japanese tertiary care hospitals using unobtrusive direct observation of physician and nurse hand hygiene adherence. Observations were performed by a trained observer on inpatient medical, surgical, intensive care, and emergency units. The primary outcom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
7
0
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 23 publications
1
7
0
1
Order By: Relevance
“…We found an increase in HH compliance by 5 moments across all healthcare workers and unit types with implementation of multimodal HH interventions, similar to findings of previous reports [15,18,19]. Comparing other moments and healthcare workers, HH compliance was generally lower for before touching a patient and after contact with patient surroundings, while compliance was lower among interns and cleaners.…”
Section: Discussionsupporting
confidence: 89%
“…We found an increase in HH compliance by 5 moments across all healthcare workers and unit types with implementation of multimodal HH interventions, similar to findings of previous reports [15,18,19]. Comparing other moments and healthcare workers, HH compliance was generally lower for before touching a patient and after contact with patient surroundings, while compliance was lower among interns and cleaners.…”
Section: Discussionsupporting
confidence: 89%
“…11,12,28,29,38 It also reflects the assertion outlined in other studies that multimodal interventions are necessary for sustained improvement. 26,39,40 Easing concerns about the system's accuracy and increasing comfort were important considerations. Our primary strategy to mitigate these concerns was to provide personalized coaching by accompanying staff members on their rounds while showing them their data in real time.…”
Section: Discussionmentioning
confidence: 99%
“…We expected that both would increase as a result of the initiative but did not expect that the 2 variables would show such a strong correlation. A prior study from Japan [41] suggested that compliance would be improved by increasing the HHSAF score. In this study, the HH compliance rate obtained by direct observation and the HHSAF scores were compared between 3 Japanese hospitals; they ranked in the same order for both measurements.…”
Section: Discussionmentioning
confidence: 99%